JURIDICAL REVIEW CONCERNING INTELLIGENT AND WITHOUT RIGHTS TO DISTRIBUTE AND/OR TRANSMIT AND/OR ACCESS ELECTRONIC INFORMATION AND/OR ELECTRONIC DOCUMENTS THAT HAVE A CONTAMINATION AND/ OR DEFAULT (Study of Decision Number 204/Pid.Sus/2021/PN Tjk) - Dimas Bahtera Setyohadi; Baharudin Baharudin; Anggalana Anggalana (UNTAG Law Review, 2022)
This research was conducted with the aim of knowing how the criminal act of defamation according to the Criminal Code and how the criminal act of defamation according to Law Number 19 of 2016 concerning ITE. By using a normative juridical research method, it is concluded: 1. The crime of defamation is regulated in detail in the Criminal Code. The Criminal Code is formulated in Articles 310 and 311 of the Criminal Code. the elements of defamation or insult according to Article 310 of the Criminal Code are: 1. intentionally; 2. to attack honor or reputation; 3. accuses of committing an act; 4. broadcast the accusations for public knowledge. If these elements of insult or defamation are only spoken (verbally insulting), then the act is classified in Article 310 paragraph 1 of the Criminal Code. However, if these elements are carried out by means of letters or pictures that are broadcast, shown or pasted (blasphemed with letters), the perpetrator can be charged with or subject to legal sanctions in Article 310 paragraph 2 of the Criminal Code. However, not all criminal acts of defamation can be punished, if the act is clearly committed in the public interest or forced to defend themselves (Article 310 paragraph 3 of the Criminal Code).